PLATONIC DIALOGUE AND GADAMERIAN HERMENEUTICS - Joni, Albertus (LOGOS, 2021)
This paper will elaborate the different Platonic elements of dialogue as philosophical basis for Gadamerian hermeneutical structures. The intersubjective cross-examination found in Plato’s Dialogue shows that the real meaning comes from the real encounters between speakers; or in Gadamer’s term: encounters between text and the reader. For Gadamer, it is always important in this pursuit of meaning and truth that we examine our own prejudice. Cross-examining our own claim of truth and belief is an essential element in Gadamer’s hermeneutics. I argue that we can see how the Platonic model of dialogue is easily aligned with the Gadamerian positive approach towards ‘traditions.’ There is a constant dialogue at work in interpretation, a dialogue between the past and the present, between different traditions and points of view. Dialogue is an important keyword for both Plato and Gadamer in their efforts to their existential quest of wisdom.